2020
DOI: 10.31489/2020ch1/60-67
|View full text |Cite
|
Sign up to set email alerts
|

Features of the extraction of yttrium and lanthanum with an intergel systembased on hydrogels of polyacrylic acid and poly-4-vinylpyridine

Abstract: Features of the extraction of yttrium and lanthanum with an intergel system based on hydrogels of polyacrylic acid and poly-4-vinylpyridine To predict the sorption activity and selectivity of hydrogels, the effect of mutual activation of polymer networks in the intergel system was studied. The intergel system of the hydrogel of polyacrylic acid ((hPAA)) and the hydrogel of poly-4-vinylpyridine (hP4VP), which was studied at a distance through the volume of the solvent in the absence of direct contact between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The features of the interaction of two hydrogels in the presence of yttrium nitrate direct contact are studied by the authors and described in detail in the figure and graphs. [13][14][15][16][17][18] Fig. 1a shows changes in the specific electrical conductivity of the aqueous medium in the presence of two hydrogels gPMAA:gP4VP and in the absence of contact between them.…”
Section: Resultsmentioning
confidence: 99%
“…The features of the interaction of two hydrogels in the presence of yttrium nitrate direct contact are studied by the authors and described in detail in the figure and graphs. [13][14][15][16][17][18] Fig. 1a shows changes in the specific electrical conductivity of the aqueous medium in the presence of two hydrogels gPMAA:gP4VP and in the absence of contact between them.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier studies [2][3][4][5][6][7][8][9][10][11][12] showed that almost all intergel systems based on acidic (polyacrylic and polymethacrylic acids) and basic (poly-4-vinylpyridine and poly-2-methyl-5-vinylpyridine) rare-crosslinked polymer hydrogels exhibit higher activity than their constituents. Moreover, it was found that the ratio of polymers, at which a high sorption of ions is manifested, differ significantly depending on the nature of acidic and basic hydrogels and the nature of rare earth metals.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of extensive studies of the rare-earth metals sorption by interpolymer systems consisting of crosslinked polyelectrolytes that undergo a remote interaction, the following advantages of new sorption methods were established [ 46 , 47 ]: Possibility of development of selective sorbents (or sorption systems) for selective sorption of aimed metal ion; Possibility of developing several selective sorbents for sorption of different metals ions on the basis of one interpolymer system; Possibility of application of rather cheap industrial ion-exchangers for creation of interpolymer systems for further sorption of aimed metals ions; Remote interaction provides the transition of each initial component into highly ionized state in interpolymer systems. Each ionized (activated) ion-exchanger can be used as an independent sorbent, which have high sorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of extensive studies of the rare-earth metals sorption by interpolymer systems consisting of crosslinked polyelectrolytes that undergo a remote interaction, the following advantages of new sorption methods were established [46,47]:…”
Section: Introductionmentioning
confidence: 99%